The Self-Potential Anomaly Produced by a Subsurface Flow at the Contact of Two Horizontal Layers and Its Quantitative Interpretation - Georgios Aim. Skianis (International Journal of Geophysics)
In the present paper the problem of a polarized cylinder with a small cross-section, which is located at the contact of two horizontal layers with different resistivities, is studied. Such a polarization geometry simulates the self-potential (SP) field produced by a horizontal flow at the contact between the two layers. First, the expression of the self potential at the space domain is derived, applying the image technique. Then, the expression for the Fourier transform of the SP anomaly is found and the behavior of the amplitude spectrum is studied. Based on this study, a direct interpretation method at the spatial frequency domain is proposed, in order to calculate the depth of the flow and the reflection coefficient of the stratified medium. Experimentation with a synthetic model shows that the method works well (small deviations between true and calculated values). When the SP curve contains noise, deviations between calculated and true depths are smaller than those between calculated and true reflection coefficients. The proposed method, which is also applied on SP data from a geothermal system (Mauri et al., 2010), may be useful in detecting underground water or heat flows.